Technical and vocational education training and industry collaboration: a bibliometric review - Omar, Marlissa; Kamaruzaman, Fathiyah Mohd (Journal of Education and Learning (EduLearn), 2024)
Technical and vocational education training (TVET) is an education and training process with a strong emphasis on industry practices that aims to generate competent workers in particular fields. Collaboration with industry in TVET has the potential to improve the quality and relevance of TVET programmes and equip students with the practical skills and knowledge demanded by employers. Thus, there is a need for a complete bibliometric study of research linked to collaboration between TVET and industry, despite the fact that the number of studies in this field continues to increase. The bibliometric analysis in this research which was extracted from Web of Science database is analyze using VOSviewer. The research conducted a descriptive analysis of the publication number trends, the top authors and leading journals in this field. Next, the researcher also analyzed the co authorship based on authors and countries, research trends, citation and keywords analysis as well as co citation analysis. The article found that most of the articles in this field are published by authors from developed countries where the majority is from the United States. Other than that, the recent research hotspot were also identified indicating the future direction of the research in this field.